Capitalismo transnacional y desarrollo nacional - Sunkel, Osvaldo; Fuenzalida, Edmundo F. (Estudios Internacionales, 1978)
During the last three decades, in most of the so-called underdeveloped countries, the process of capitalist development has notably expanded and deepened. We argue that the process of development of national societies in that time has been largely conditioned by the appearance of a new type of global system originated by the world expansion of oligopolistic techno-industrial capitalism in its new stage of transnational organization. The present work tries to sketch in a summary and provisional way the nature of this new global system, its main components and their interrelations, its historical roots in the crisis of a previous phase of global organization of industrial capitalism, and finally, the way in which its presence conditions the development process of national societies.